Historias hiladas: La introducción de aves andinas en la plumaria novohispana - Erika Escutia (Nuevo mundo - Mundos Nuevos, 2025)
The study delves into the fascinating history of using Andean duck downs as raw material for producing textiles in New Spain during the second half of the 16th century. The article identifies specifically the species Cairina Moschata as the one to which primary sources refer under the names of Peruvian duck and Perutototl and discusses its introduction, and acclimatization in various regions of New Spain. It also sheds light on how female communities of artisans, experts in textile and featherwork, embraced this novel material. Through the analysis of material culture and the social history of art, this article offers insights into the political, economic, and productive conditions of the feather craftswomen and their relationship with the Andean duck feathers at the dawn of New Spain.